Perancangan Perancangan Sistem Penjadwalan Otomasi Petugas Vidiotron di Dinas Komunikasi dan Informatika Situbondo - Mohammad Agil; Ahmad. Homaidi; Iqbal Hamdani W.M (LKP Unity Academy, 2025)
This study discusses the design of an automated scheduling system for vidiotron staff at the Department of Communication and Informatics of Situbondo, with the aim of developing a web-based system that simplifies scheduling, task distribution, and staff data management in a structured and efficient manner. The research method includes requirements analysis, input design, process design, application architecture, and system modeling using Unified Modeling Language (UML). The results of this study produce a system design featuring user login, staff data input, activity scheduling, automated scheduling, report and documentation storage, as well as the ability to download schedules in PDF format. In conclusion, this automated scheduling system can reduce delays, irregular task assignments, and support the smooth operation of vidiotron activities, while future research is expected to continue to the coding stage to produce a fully functional web-based application.